Actualization of the Properties of the Teacher in the Qur'an - Sya’ban Abdul Karim (Pusdikra-Publishing.com, 2023)
A recent Problem faced by educators is the blatant opposition made by students to parents. It is not uncommon for violence to occur between teachers and students to the point that reporting to the authorities is inevitable. This paper aims to explain the qualities that must be possessed by an educator based on the information contained in the Qur'an. This study is a qualitative research literature study with descriptive analysis approach. The primary data source in this paper is Qs. Verses 1-4 and Surah al-Rahman. An-Nahl verses 43-44. The results showed that an educator must have the nature of loving and merciful Rahman, sincere in educating students, have a good public speaking, able to design a learning plan optimally, a source of knowledge for students, educators understand the duties and functions as well as his role as an educator and make the Prophet as a guide in teaching.